Lipid regulation of hERG1 channel function - Williams E. Miranda (Nature Portfolio, 2021)
The lipid regulation of mammalian ion channel function has emerged as a fundamental mechanism in the control of electrical signalling and transport specificity. Here, the authors combine molecular dynamics simulations, mutagenesis, and electrophysiology to provide mechanistic insights into how lipophilic molecules alter gating kinetics and K+ currents of hERG1.